Salivary steroids and psychometric parameters in male marathon runners. Issue 2 (June 1989) - Harris, B; Cook, N J; Walker, R F; Read, G F; Riad-Fahmy, D
Abstract : Testosterone and cortisol in male marathon runners (n = 11) were determined in saliva samples (n = 28) collected during the three rest days preceding a competitive marathon and in the samples collected at 08.00h on the race day. An Eysenck Personality Inventory was completed on the first rest day and psychological state was assessed on rest days and on the morning of the marathon by completion of visual analogue scales for anxiety, depression, hostility and libido at four times each day. Anxiety, depression and hostility were positively inter-correlated. Extraversion and depression were negatively correlated. At 08.00h on the day of the marathon, anxiety and hostility scores were significantly higher than those on rest days, but depression and libido scores were unchanged. No relationship was found between depression or libido and any hormonal parameter. Race day cortisol correlated negatively with hostility, and changes in cortisol (09.00h) between the race day and the mean rest-day levels correlated with the corresponding changes in anxiety.